Coordination of diabetic retinopathy screening in the Kimberley region of Western Australia. (18th April 2016) - Moynihan, Verity; Turner, Angus
Abstract: Objective: To determine the coverage provided by the Kimberley Diabetic Retinopathy Screening Program and evaluate the impact of the Kimberley diabetic eye health coordinator (KDEHC) position using an evidence‐based approach. Design: Retrospective audit. Setting: Primary care services in the Kimberley region of Western Australia. Participants: Individuals with diabetes mellitus who underwent screening for diabetic retinopathy (DR) from 1 March 2010 to 28 February 2014. Interventions: A KDEHC was engaged from February 2012 to provide coordination and support for the DR screening program. Main outcome measure(s): Coverage provided by the program for Indigenous Australians with diabetes, as measured against annual projected needs for diabetic eye examinations. Results: Data were collected for 1247 screening episodes for 947 Indigenous Australian patients. Coverage provided by the program increased from 9.44% in 2010–2011 to 29.8% in 2013–2014 ( P < 0.05). The number of sites engaged in screening increased from four in 2010–2011 to 17 in 2013–2014. After the engagement of the KDEHC, significant increases in visual acuity recording and coverage were observed, as well as a non‐significant increase in photo quality. Conclusions: Engagement of the KDEHC was associated with significant increases in program coverage. Despite the observed increase, there were significant shortfalls in the number of Indigenous Australians with diabetes undergoing screening in the Kimberley region. This may be explained by examinations provided by other services in the Kimberley region, namely visiting optometry services, but also highlights a large proportion of the population not undergoing screening.